2021
DOI: 10.1002/jsfa.11148
|View full text |Cite
|
Sign up to set email alerts
|

Lily bulbs’ polyphenols extract ameliorates oxidative stress and lipid accumulation in vitro and in vivo

Abstract: BACKGROUND Polyphenols have the potential to reduce the risk of many metabolic disorders. Lily bulbs are rich in polyphenols; however, their effects on lipid metabolism remain unclear. This study aimed to explore the effects of lily bulbs’ polyphenols (LBPs) on oxidative stress and lipid metabolism. RESULTS A total of 14 polyphenolic compounds in LBPs were identified by high‐performance liquid chromatography equipped with diode‐array detection mass spectrometry. Total phenolic compound in LBPs was 53.76 ± 1.12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Lily Bulbs have an excellent antioxidant capacity. [15,16] According to Kan et al [17] , Lily Bulbs Rehmannia inhibits adipocyte differentiation and adipogenesis. [18] It also plays an antioxidative role in improving the bone structure of osteoporosis rats by improving muscle atrophy.…”
Section: Discussionmentioning
confidence: 99%
“…Lily Bulbs have an excellent antioxidant capacity. [15,16] According to Kan et al [17] , Lily Bulbs Rehmannia inhibits adipocyte differentiation and adipogenesis. [18] It also plays an antioxidative role in improving the bone structure of osteoporosis rats by improving muscle atrophy.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that selective PPARα agonists and overexpression of PPARα can partially inhibit FASN mRNA in HB2 cells (Iizuka et al, 2013), which is consistent with our research results. The latest research shows that when the expression of PPARα is upregulated, the expression of SCD is downregulated, which may also imply the negative regulatory effect of PPARα on FASN and SCD (Gong et al, 2021; Kan et al, 2021; Zhang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Fat synthesis is an important pathway in the process of lipid FASN is focussed mainly on some diseases in mammals and humans (Menendez, 2007;Menendez et al, 2009). SCD is a key rate- that when the expression of PPARα is upregulated, the expression of SCD is downregulated, which may also imply the negative regulatory effect of PPARα on FASN and SCD (Gong et al, 2021;Kan et al, 2021;Zhang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…38 A study found that phenolics from lily bulbs significantly reduced weight gain and oxidative damage in mice on a high-fat diet in a manner dependent on the dose. 39 Chronic diseases have been shown to be linked to oxidative stress, and plant phenolics can act as antioxidants to combat these diseases. 40 Ferulic acid is a natural phytochemical with various biological activities, including anticarcinogenic, antidiabetic, hepatoprotective, cardioprotective, and neuroprotective properties.…”
Section: Classification Of Phenolicsmentioning
confidence: 99%
“…43 In cellular experiments, phenolics in the lily bulb could block ROS production, alleviate oxidative stress, and reduce lipid accumulation in HepG2 cells. 39 Studies have shown that regularly consuming phenolics-rich beverages could also effectively control oxidative stress. Red wine phenolics have been found to ameliorate excess superoxide production induced by a high-fat diet in the pancreas, liver, and blood vessels.…”
Section: Classification Of Phenolicsmentioning
confidence: 99%